Plasma Epstein‐Barr virus DNA for pediatric Burkitt lymphoma diagnosis, prognosis and response assessment in Malawi. Issue 11 (24th March 2017) - Westmoreland, Katherine D.; Montgomery, Nathan D.; Stanley, Christopher C.; El‐Mallawany, Nader Kim; Wasswa, Peter; van der Gronde, Toon; Mtete, Idah; Butia, Mercy; Itimu, Salama; Chasela, Mary; Mtunda, Mary; Kampani, Coxcilly; et al.
Abstract : Point‐of‐care tools are needed in sub‐Saharan Africa (SSA) to improve pediatric Burkitt lymphoma (BL) diagnosis and treatment. We evaluated plasma Epstein–Barr virus (pEBV) DNA as a pediatric BL biomarker in Malawi. Prospectively enrolled children with BL were compared to classical Hodgkin lymphoma (cHL) and nonlymphoma diagnoses. Pediatric BL patients received standardized chemotherapy and supportive care. pEBV DNA was measured at baseline, mid‐treatment, and treatment completion. Of 121 assessed children, pEBV DNA was detected in 76/88 (86%) with BL, 16/17 (94%) with cHL, and 2/16 (12%) with nonlymphoma, with proportions higher in BL versus nonlymphoma ( p < 0.001) and similar in BL versus cHL ( p = 0.69). If detected, median pEBV DNA was 6.1 log10 copies/mL for BL, 4.8 log10 copies/mL for cHL, and 3.4 log10 copies/mL for nonlymphoma, with higher levels in BL versus cHL ( p = 0.029), and a trend toward higher levels in BL versus nonlymphoma ( p = 0.062). pEBV DNA declined during treatment in the cohort overall and increased in several children before clinical relapse. Twelve‐month overall survival was 40% in the cohort overall, and for children with baseline pEBV detected, survival was worse if baseline pEBV DNA was ≥6 log10 copies/mL versus <6 log10 copies/mL ( p = 0.0002), and also if pEBV DNA was persistently detectable at mid‐treatment versus undetectable ( p = 0.041). Among children with baseline pEBV DNA detected, viremia was the only significant risk factor for death by 12 months in multivariate analyses (adjusted hazard ratio 1.35 per log10 copies/mL, 95% CI 1.04–1.75, p = 0.023). Quantitative pEBV DNA has potential utility for diagnosis, prognosis, and response assessment for pediatric BL in SSA. Abstract : What's new? Burkitt lymphoma (BL) is the most frequent childhood cancer in sub‐Saharan Africa. Although it is highly curable in resource‐rich settings, outcomes are much worse in the region and point‐of‐care tools are needed to improve diagnosis and treatment. Epstein–Barr virus (EBV) is causally associated with the most common endemic form of the disease. This is the first study to systematically assess plasma EBV DNA for pediatric BL diagnosis, prognosis, and response assessment in sub‐Saharan Africa. The results show that plasma EBV DNA may be an implementable biomarker to facilitate diagnosis and risk‐stratified, response‐guided therapy for this challenging population in the region.